Effects of selenium on thyroid hormone levels in sheep - Atessahin, A; Pirinçci, I; Gürsu, F; Çikim, G (Scientific Technical Research Council Turkey, 2002)
In this study, the thyroid hormone levels in sheep experimentally treated with selenium were investigated. Twelve Akkaraman sheep were used in the investigation. Selenium was given intramuscularly at doses of 0.1 (Group 1) and 0.4 mg/kg (Group 2). The blood samples were taken from the jugular vein at 1, 2, 4, 8, 24, 48, 96 and 144 hours after the administration. Serum triiodotyronine (T3), thyroxin (T4), free triiodotironine (fT3) and free thyroxin (fro) levels were determined using a hormone autoanalyzer. In the comparison between the groups, it was shown that serum T3 levels reached the maximum levels at the 96(th) and 48(th) hours; fT4 levels at the 8(th) and 2(nd) hours in Groups 1 and 2, respectively. Serum fT3 levels reached the maximum level at the 2(nd) hour in Group 1 and the minimum level at the 144(th) hour in Group 2. However, serum T4 levels reached the minimum level at the 2(nd) hour in Groups 1 and 2. In conclusion, an increase in serum T3, fT3 (Group 1) and fT4 levels in sheep given selenium was observed, while a decrease in T4 and fT3 (Group 2) levels was seen.
Koyunlarda selenyumun tiroid hormon düzeyleri üzerine etkileri
Keywords: sheep; selenium; thyroid hormone